Description of two new damselflies, Protosticta zhengi and Sinosticta sylvatica, from China (Odonata: Zygoptera: Platystictidae) - Yu, Xin; Bu, Wenjun (Zootaxa, 2009)
Two new species of Platystictidae (Sinosticta sylvatica, holotype male: China, Hainan, Diaoluoshan Nature Reserve, 620m, 29-V-2007; and Protosticta zhengi, holotype male; China, Yunnan, Xishuangbanna, Menghun, 750m, 30-V-1958; both deposited in Institute of Entomology, Nankai University, Tianjin, China) are described, and a key is provided for the identification of all described species of Sinosticta Wilson.